Inhibition of drug-metabolizing enzymes by Qingfei Paidu decoction: Implication of herb-drug interactions in COVID-19 pharmacotherapy - Zhang, Feng (Food Chem Toxicol, 2021)
Corona Virus Disease 2019 (COVID-19) has spread all over the world and brings significantly negative effects on human health. To fight against COVID-19 in a more efficient way, drug-drug or drug-herb combinations are frequently used in clinical settings. The concomitant use of multiple medications may trigger clinically relevant drug/herb-drug interactions. This study aims to assay the inhibitory potentials of Qingfei Paidu decoction (QPD, a Chinese medicine compound formula recommended for combating COVID-19 in China) against human drug-metabolizing enzymes and to assess the pharmacokinetic interactions in vivo. The results demonstrated that QPD dose-dependently inhibited CYPs1A, 2A6, 2C8, 2C9, 2C19, 2D6 and 2E1 but inhibited CYP3A in a time- and NADPH-dependent manner. In vivo test showed that QPD prolonged the half-life of lopinavir (a CYP3A substrate-drug) by 1.40-fold and increased the AUC of lopinavir by 2.04-fold, when QPD (6 g/kg) was co-administrated with lopinavir (160 mg/kg) to rats. Further investigation revealed that Fructus Aurantii Immaturus (Zhishi) in QPD caused significant loss of CYP3A activity in NADPH-generating system. Collectively, our findings revealed that QPD potently inactivated CYP3A and significantly modulated the pharmacokinetics of CYP3A substrate-drugs, which would be very helpful for the patients and clinicians to avoid potential drug-interaction risks in COVID-19 treatment.